Understanding of Accountancy Graduates on the Relevant Concepts Taught in the Subject Accounting Theory at HEI in Greater Florianópolis - Fabiana Frigo Souza; Ernesto Fernando Rodrigues Vicente (Revista de Educação e Pesquisa em Contabilidade, 2017)
This research aims to identify the understanding of the undergraduate students in Accountancy about the relevant concepts taught in the discipline Accounting Theory. To reach this goal, a questionnaire was sent to selected institutions or applied in person, obtaining a total of 65 respondents who had already studied Accounting Theory. The results of this research show that students perceive the concepts related to the discipline in a way more linked to standardization and that, for most respondents, the discipline Accounting Theory was considered of fundamental importance and should not be eliminated. In addition, it cannot be affirmed that there is a relationship between the area and the time of action of the respondents and their perceptions regarding the concepts of the discipline. It was also observed that there is little discussion about some subjects, in which some students are totally unaware, like in the case of Agency Theory and Earnings Management, which may indicate a gap in the teaching of the discipline. For future research, the analysis of distance learning is suggested, as well as research that seeks to analyze the existence of this possible gap observed.